한중간 철강유통산업의 경쟁력 비교분석 - 이재승; 정명희; Lee, Jae-Sung; Jung, Myung-Hee (Journal of distribution science, 2014)
Purpose - This research undertakes to understand the competitiveness of the steel distribution industry of both Korea and China to strengthen Korea-Sino economic cooperation, examines impediments to trade between the two countries to analyze causes which affect trade, and examines improvements in these areas to identify means of trade expansion. Through this survey of a defined period, we can identify the structural factors of trade dependence in the relationship between Korea and China. Research design, data, and methodology - The data were collected from the Korea Traders Association, the Korea Customs Office, and UN Comtrade, from which whole table indexes are calculated. The research methodology uses trade-related indexes to focus on analyzing comparative advantages based on time-series analysis statistics data (2000-2012) by using the analysis index of trade intensity index (TII), the revealed comparative advantage index (RCA), and the trade specialization index (TSI). Results - The export ratio for Korea to China was slightly higher in 2000 at 2.867, and the export ratio for Korea to China was sustained in 2005. However, it diminished gradually, reaching 1.263 in 2012. During the period 2000-2012, the indexes were maintained without any significant change. However, they still remain close to -1. In particular, in 2012 it is the closest it has ever been to -1. Therefore, China has a comparative advantage in export specialization. On the other hand, Korea has a comparative advantage in import specialization. For the research period, all indexes were much lower than 1, which means that Korea has consistently had a comparative disadvantage against China for the past 10 years when compared to other industries, even though it experienced improvement in 2000. Conclusions - The summary of conclusions based on empirical analysis research are as follows: First, per the trade intensity index of industries between the two countries, we conclude that the export ratio index in 2000 is 2.867, which means the export ratio of Korea to China is slightly higher. Furthermore, the ratios of 2.259 and 1.263 held in 2005 and 2012, respectively, meaning that the export ratio of Korea to China was maintained in 2005, but was diminishing gradually as the index in 2012 was 1.263. Second, per the trade specialization index of the steel distribution industry between Korea and China, the value was -0.379 in 2000, -0.368 in 2005 and -0.568 in 2012. Looking at the whole period of 2000-2012, the indexes remained without any significant change. However, they are still moving closer to -1. In particular, in 2012 it is the closest it has ever been to -1. Third, regarding the revealed comparative advantage index of the steel distribution industry between Korea and China, the RCA indexes in 2005 and 2012 are 0.246 and 0.306, respectively, which are still far from 1, even though the index has improved compared to the 2000's value of 0.0001. Therefore, the Korean steel distribution industry is at a significant comparative disadvantage to that of the Chinese steel distribution industry.